STRATEGI MENGGALI MINAT MASYARAKAT UNTUK MEMAKAI JASA UNGGULAN DI BMT NUANSA UMAT CABANG PURWOHARJO - Afria Rachmawati (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2023)
This research is to find out the strategies that should be used in offering mobile service and using the products of the BMT Nuansa Umat Purwoharjo. The strategy is used so that people are interested in saving money at BMT NU which carries the slogan ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œServing Without Limits Serving SincerelyÃƒÂ¢Ã¢â€šÂ¬Ã‚Â. The method used is Descriptive Qualitative. The research was conducted at BMT NU Branch Purwoharjo with the research subject being the marketing of each product offering program or Nuansa Umat saving program to customers/ members or general customers. The marketing strategy for superior service products used by the BMT NU Purwoharjo branch is to determine the publics interest in saving, namely by using several strategies, namely by identifying internal and external factors. Besides that, ait also prioritizes excellent service, honest and trustworthy and can be relied on.